2016
DOI: 10.1038/srep22569
|View full text |Cite
|
Sign up to set email alerts
|

Specific LED-based red light photo-stimulation procedures improve overall sperm function and reproductive performance of boar ejaculates

Abstract: The present study evaluated the effects of exposing liquid-stored boar semen to different red light LED regimens on sperm quality and reproductive performance. Of all of the tested photo-stimulation procedures, the best pattern consisted of 10 min light, 10 min rest and 10 min of further light (10-10-10 pattern). This pattern induced an intense and transient increase in the majority of motility parameters, without modifying sperm viability and acrosome integrity. While incubating non-photo-stimulated sperm at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
45
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 65 publications
16
45
2
Order By: Relevance
“…The process of pulse optimization involves the experimental evaluation of two parameters: the period of time needed for light of a certain wavelength and intensity to elevate the mitochondrial ATP levels in a well defined environment, and the period of time in which the cells exhaust the ATP stores. This approach, proposed by us in recent paper (22), was experimentally confirmed in a boar sperm model (23). Once the individual parameters are known it is possible to adjust the duration of the light pulse and the dark period between pulses to a balanced ratio accounting for the specific energy demand of the cell.…”
Section: Nanodiamond For Ivfmentioning
confidence: 89%
“…The process of pulse optimization involves the experimental evaluation of two parameters: the period of time needed for light of a certain wavelength and intensity to elevate the mitochondrial ATP levels in a well defined environment, and the period of time in which the cells exhaust the ATP stores. This approach, proposed by us in recent paper (22), was experimentally confirmed in a boar sperm model (23). Once the individual parameters are known it is possible to adjust the duration of the light pulse and the dark period between pulses to a balanced ratio accounting for the specific energy demand of the cell.…”
Section: Nanodiamond For Ivfmentioning
confidence: 89%
“…A recent study has shown that red light from LEDs can increase sperm quality by increasing swimming speed and mitochondrial membrane potential3. However, DNA damage was not tested in this the study.…”
mentioning
confidence: 93%
“…Light‐emitting diodes (LED) can be effective alternative light sources, providing advantages such as broad beam width and cost‐efficiency (Rohringer et al., ). Recent reports indicate that exposure of liquid‐stored boar semen to red LED‐based light improves sperm quality and reproductive performance in sow herds (Balasch & Rodríguez, ; Yeste et al., ). This might be especially beneficial for hypothermically stored boar semen suffering from loss of sperm function.…”
Section: Introductionmentioning
confidence: 99%